2009
DOI: 10.1266/ggs.84.153
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive phylogeny of the family Sparidae (Perciformes: Teleostei) inferred from mitochondrial gene analyses

Abstract: Sparid fishes consist of approximately 115 species in 33 genera that are broadly distributed in tropical and temperate coastal waters. Although several phylogenetic analyses were conducted based on specific molecular markers, their classification remains unresolved. Here, we present the most comprehensive molecular phylogeny of the family Sparidae to date, based on cytochrome b (cyt-b) genes. We determined 18 sequences of sparids and conducted phylogenetic analyses among 72 individuals representing 66 sparids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
52
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 61 publications
10
52
1
Order By: Relevance
“…El-Agamy, 1989;Radebe et al, 2002;Kailola et al, 1993;Willis et al, 2003;Hughes et al, 2008;Al Mamry et al, 2009;Kraljević et al, 1996). The taxonomy and phylogeny of the family Sparidae has have been revised several times (de la Herran et al, 2001;Chiba et al, 2009;Hanel & Sturmbauer, 2000), but remains controversial. Morphological characters such as body shape, arrangement of fins, color and identification marks (blotches, bars, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El-Agamy, 1989;Radebe et al, 2002;Kailola et al, 1993;Willis et al, 2003;Hughes et al, 2008;Al Mamry et al, 2009;Kraljević et al, 1996). The taxonomy and phylogeny of the family Sparidae has have been revised several times (de la Herran et al, 2001;Chiba et al, 2009;Hanel & Sturmbauer, 2000), but remains controversial. Morphological characters such as body shape, arrangement of fins, color and identification marks (blotches, bars, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In all, dentition has been a key character to differentiate between different genera and species (Chiba et al, 2009;Orrell et al, 2002;Day, 2002). Molecular techniques have been proved useful in resolving most of the issues of the classification of the species of family sparidae (Chiba et al, 2009). First two dorsal spines short, 3rd and 7 th elongated, filamentous (especially in juveniles and subadults) .…”
Section: Introductionmentioning
confidence: 99%
“…The above conflict is maintained till today; although karyological studies (Vasiliev, 1980) as well as genetic studies (Chiba et al, 2009;Imsiridou et al, 2011;Turan, 2011) undoubtedly prove that S. maena and S. flexuosa are two different species. Assuming that S. maena and S. flexuosa are two different species, identification is possible using meristic and morphometric characteristics (Tortonese, 1986;Fischer et al, 1987;Rizkalla, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, Spicara maena (L.) has been classifi ed within the family Centracanthidae (see Tortinese, 1986) and even used as the outgroup in molecular phylogenetic analyses of the Sparidae (see Hanel & Sturmbauer, 2000). However, subsequent studies supported a monophyletic Sparidae with the inclusion of the centracanthid genus Spicara Rafi nesque (see Orrell et al, 2002;Orrell & Carpenter, 2004;Chiba et al, 2009). These authors also suggested that the feeding types traditionally used for defi nition of subfamilies within the Sparidae, were independently derived multiple times; multiple transitions from a durophagous to a non-durophagous diet were also suggested by Santini et al (2014).…”
Section: Introductionmentioning
confidence: 99%